Explaining the impact of a women's group led community mobilisation intervention on maternal and newborn health outcomes: the Ekjut trial process evaluation - Sinha Rajesh; Bajpai Aparna; Gope Rajkumar; Mahapatra Rajendra; Rath Shibanand; Barnett Sarah; Tripathy Prasanta K; Nair Nirmala; Rath Suchitra; Costello Anthony; Prost Audrey (BMC, 2010)
Abstract Background Few large and rigorous evaluations of participatory interventions systematically describe their context and implementation, or attempt to explain the mechanisms behind their impact. This study reports process evaluation data from the Ekjut cluster-randomised controlled trial of a participatory learning and action cycle with women's groups to improve maternal and newborn health outcomes in Jharkhand and Orissa, eastern India (2005-2008). The study demonstrated a 45% reduction in neonatal mortality in the last two years of the intervention, largely driven by improvements in safe practices for home deliveries. Methods A participatory learning and action cycle with 244 women's groups was implemented in 18 intervention clusters covering an estimated population of 114 141. We describe the context, content, and implementation of this intervention, identify potential mechanisms behind its impact, and report challenges experienced in the field. Methods included a review of intervention documents, qualitative structured discussions with group members and non-group members, meeting observations, as well as descriptive statistical analysis of data on meeting attendance, activities, and characteristics of group attendees. Results Six broad, interrelated factors influenced the intervention's impact: (1) acceptability; (2) a participatory approach to the development of knowledge, skills and 'critical consciousness'; (3) community involvement beyond the groups; (4) a focus on marginalized communities; (5) the active recruitment of newly pregnant women into groups; (6) high population coverage. We hypothesize that these factors were responsible for the increase in safe delivery and care practices that led to the reduction in neonatal mortality demonstrated in the Ekjut trial. Conclusions Participatory interventions with community groups can influence maternal and child health outcomes if key intervention characteristics are preserved and tailored to local contexts. Scaling-up such interventions requires (1) a detailed understanding of the way in which context affects the acceptability and delivery of the intervention; (2) planned but flexible replication of key content and implementation features; (3) strong support for participatory methods from implementing agencies.